Asymmetric syntheses of the pseudodistomin alkaloids - Zimmer, D (2018)
This thesis centres on asymmetric syntheses of the pseudodistomin alkaloids, initially targeting a member of the family that had yet to be subjected to laboratory synthesis, followed by the development and execution of a unified strategy for the synthesis of all of the known pseudodistomin alkaloids as well as non-natural analogues. Chapter 1 presents a comprehensive and critical review of all literature reports relating to the isolation, structural elucidation and syntheses of the pseudodistomin alkaloids to date, culminating in the realisation of aims for this thesis. Chapter 2 describes the first total asymmetric synthesis of pseudodistomin E, culminating in confirmation of the assigned absolute configuration and correlation with the 1H and 13C NMR spectroscopic data originally reported for the natural product in the isolation study. Chapter 3 reviews the first-generation synthesis and details the evaluation of a range of model systems to facilitate the development of a unified strategy for the synthesis of the pseudodistomin alkaloids and non-natural analogues, culminating in an optimised proposed synthetic strategy. Chapter 4 discusses the development and execution of a general strategy for the asymmetric syntheses of the pseudodistomin alkaloids, culminating in the total asymmetric syntheses of all of the known pseudodistomin alkaloids and a representative non-natural analogue. Chapter 5 offers independent assignments of the relative and absolute configurations of the pseudodistomin alkaloids, followed by a comparison of spectroscopic data with literature reports, culminating in correlation with the data provided for the natural materials. Chapter 6 contains full experimental procedures and characterisation data for all compounds synthesised in Chapters 2–4.